PENGEMBANGAN MEDIA PEMBELAJARAN KEANEKARAGAMAN HAYATI BERBASIS ANDROID UNTUK SISWA KELAS V SEKOLAH DASAR - Esti Aulia Rahma Dani; Prasena Arisyanto; Wawan Priyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem in this study is the lack of use of learning media, especially in natural and social science materials (IPAS). This results in students being less motivated to learn. The purpose of this research is to produce Android-based biodiversity learning media that is valid and practical for grade 5 elementary school students. The research method used is research and development (R&D) with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The samples in this study were teachers and 5th grade students of SD Negeri 1 Sidomulyo.The results of the study state that biodiversity learning media are valid and practical. Media validity is obtained from media expert validation 94% and material expert validation 92%. The practicality of the media is obtained from teacher respones 96% and student respones 86%. Based on the research, this media can be used as an alternative interactive learning media in schools.